Analisis Kasus Kelayakan Bisnis Percetakan Kanaya Invitation pada Dusun Ketapang - Najwa Azzahra; Arum Fiona; Ajeng Navila; Alya Nafi; Yoga Sudrajat; Andhika Dwi Kristiawan (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study aims to analyze the business feasibility of Kanaya Invitation Printing, located in Ketapang Hamlet, Susukan District, Semarang Regency. The case analysis was conducted based on six main aspects of a business feasibility study, namely legal, market and marketing, technical and operational, management and human resources, environmental, and financial aspects. This study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The results indicate that, from the legal aspect, the business has obtained a Business Certificate (Surat Keterangan Usaha/SKU), providing a legal basis for its operational activities. The market and marketing aspect shows that the business has a clearly defined target market, supported by competitive pricing, satisfactory service quality, and promotional activities through digital media and customer recommendations. From the technical and operational aspect, the production process has been well managed and supported by adequate equipment, along with plans for technological improvement. The management and human resources aspect demonstrates a clear division of responsibilities, although the business is still managed on a family basis. From the environmental aspect, the business activities do not generate significant negative impacts and have the potential to implement more environmentally friendly waste management practices. Meanwhile, the financial aspect indicates that the business is highly feasible, with a Net Present Value (NPV) of IDR 2,448,421,624.88, an Internal Rate of Return (IRR) of 124%, a Profitability Index (PI) of 16, an Average Rate of Return (ARR) of 128%, and a Payback Period (PP) of 10 months and 13 days. Based on the analysis of these six aspects, Kanaya Invitation Printing is considered feasible to operate and further develop due to its promising market prospects, effective operational system, sound business management, minimal environmental impact, adequate legal compliance, and strong financial performance. This study is expected to serve as a reference for business owners in developing their businesses and for future research on business feasibility analysis in the printing industry.